Analisis Sikap, Norma Subyektif, Kontrol Perilaku dan Pengalaman Pengguna Internet terhadap Niat dan Perilaku Berbelanja Online di Kota Malang - Balady, Mohammad Haris (Jurnal Aplikasi Manajemen, 2011)
The aim of this study is to analyze attitude, subjective norm perceived behavioral control and experience influence intention and behavior towards online shopping. This study is based on a questionnaire survey asking participants what factors inÃ¼uence their use of the internet for shopping. Population in this study is consumer online in Malang, sampling technique used was convenience sampling, data while collected through questionnaire as many as 100 respondents were taken as samples. In order to measure respondents response, the author used Likert's Scale to test the models using path analysis Analysis of the result shows that attitude, subjective norm, perceived behavioral control and experience, influence consumers' intention towards online shopping. Perceived behavioral control experience and intention influence consumers' behavior towards online shopping.